PRACTICUM BASED LEARNING DEVELOPMENT ASSISTANCE IN STATE HIGH SCHOOLS 2 BAUBAU - Fahmil Ikhsan Taharu; S Hafidhawati Andarias (Jurnal Pengabdian Pada Masyarakat MEMBANGUN NEGERI, 2020)
The management of practicum time at State Senior High School 2 Baubau was considered inefficient by the teacher because in the implementation process, the practicum took a different time from the learning hours. This service aims to integrate the teacher's practical implementation time in learning hours. This service is carried out in three stages, namely the planning, implementation, and learning analysis stages. through Focus group discussions (FGD), the teacher and the resource persons compile learning instruments and at the implementation stage of learning the teacher and resource persons collaborate to help students carry out practicum. The analysis of the learning implementation assistance process shows that students are more enthusiastic in learning because they are directly involved in learning, while in the aspect of time management the teacher feels that this learning is very efficient because it reduces the time needed to hold practicum.